Understanding Youth Participation Across Europe From Survey to Ethnography (Palgrave Macmillan UK, 2018)
This edited volume presents findings from a major cross-European research project mapping the civic and political engagement of young Europeans in the context of both shared and diverse political heritages. Drawing on new survey, interview and ethnographic data, the authors discuss substantive issues relating to young people's attitudes and activism including: attitudes to the European Union and to history; understanding of political ideologies; how attitudes to democracy are shaped by political heritage; activism in radical right wing groups and religion-based organisations; and digital activism. These contributions make the book's case that transnational and multi-method projects can enrich our understanding of how young people envisage their place and role in Europe's political and civic space. The book challenges methodological assumptions that survey research shows the big picture but at the cost of local nuance or that qualitative research cannot speak beyond the individual case, and demonstrates the added explanatory value of triangulating different kinds of data. Understanding Youth Participation Across Europe will be of interest to students and scholars across a range of disciplines, including Sociology, Political Sociology, Youth Studies and Political and Civic Participation. .